Enhancing Verbal Engagement in Diverse Classrooms: The Peer-Supported Verbal Engagement Model (PSVEM) - Quileste, Ronald; Ogoy, Djevonah; Roble, Christhie Jean; Gonzalez, Alexandria Yzzabelle; Golez, Michaela Grace; Caberoy, Wayne Mark (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
Low verbal participation remains a barrier to active learning, particularly in hybrid classrooms. This mixed-methods action research evaluated the Student-Selected Buddy System (SSBS), a peer-support intervention promoting verbal engagement through student autonomy and collaboration. Implemented in a Grade 12 STEM hybrid class, the SSBS significantly increased verbal participation (pre-test M = 2.92 to post-test M = 3.10, p < .05), with 63% of students improving. Qualitative data revealed enhanced confidence, collaboration, and the critical role of relatable topics and teacher facilitation. Addressing a gap in student-centered verbal engagement strategies, this study introduces the Peer-Supported Verbal Engagement Model (PSVEM)-a novel, theory-grounded framework integrating autonomy, peer scaffolding, and teacher support. Designed for replicability across K-12, higher education, and online/in-person modalities, PSVEM provides educators with practical, adaptable guidelines to promote inclusive dialogue. Scalable and context-flexible, PSVEM empowers teachers worldwide to boost student voice and transform classroom dynamics through peer-driven interaction.